2019
DOI: 10.1007/s00404-019-05155-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of localization and histological verification of endometrial polyps on infertility

Abstract: Aim Our purpose is to investigate if transcervical resection of endometrial polyps improves the fertility in ovulatory infertile women, and whether polyp histology, intrauterine location, and the technique of polypectomy have any influence on the pregnancy rates. Methods In this retrospective study, clinical data of 87 ovulatory infertile women who underwent hysteroscopy and polypectomy, and their 12-month follow-up have been analyzed. Subgroups according to the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Clinically, EP is a type of benign lesion in women with focal growth of the endometrial glands and stroma ( 2 ). EP affects approximately 7.8–34.9% of reproductive women and usually impairs fertility ( 3 , 4 ). Previous reports showed that assisted reproductive technology such as in vitro fertilization is required for 11–45% EP patients ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, EP is a type of benign lesion in women with focal growth of the endometrial glands and stroma ( 2 ). EP affects approximately 7.8–34.9% of reproductive women and usually impairs fertility ( 3 , 4 ). Previous reports showed that assisted reproductive technology such as in vitro fertilization is required for 11–45% EP patients ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…For AUB or infertility patients, however, surgeries including blind dilation and curettage, hysteroscopic polypectomy, and even hysterectomy could be applied to remove polyps ( 1 ). Published clinical data showed that polypectomy could effectively relieve symptoms of EP ( 3 , 4 ). Nevertheless, infertility is a common issue in EP patients of reproductive-age ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore clinical evidence suggesting that polypectomy should be considered in infertile women. The same study suggests that when histology confirms normal or functional EPs, there is no evidence supporting that their presence has an impact on fertility [17].…”
Section: Current Opinion In Gynecology and Obstetricsmentioning
confidence: 94%
“…The exact mechanism corelating EPs and fertility issues remains still unknown. Lőrincz et al [17], has shown that polypectomy improved the conception rate in the subsequent years regardless of the intrauterine localization and the exact method of its surgical removal. There is therefore clinical evidence suggesting that polypectomy should be considered in infertile women.…”
Section: Current Opinion In Gynecology and Obstetricsmentioning
confidence: 99%
“…Some studies focus on infertility with a clear etiology. According to Lőrincz et al , polypectomy can boost the fertility rate in the following year in infertile women regardless of the surgical resection methods ( 16 ). Using multivariate logistic regression analysis, Adedigba et al found that women who did not have hydrosalpinx were less likely to be infertile than those who did.…”
Section: Introductionmentioning
confidence: 99%